2017
DOI: 10.1186/s12879-017-2205-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of gene expression during immunisation trial against Fasciola hepatica: identification of genes and pathways involved in conferring immunoprotection in a murine model

Abstract: BackgroundFasciolosis remains a significant food-borne trematode disease causing high morbidity around the world and affecting grazing animals and humans. A deeper understanding concerning the molecular mechanisms by which Fasciola hepatica infection occurs, as well as the molecular basis involved in acquiring protection is extremely important when designing and selecting new vaccine candidates. The present study provides a first report of microarray-based technology for describing changes in the splenic gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Transcriptomic analysis of PBMCs from sheep revealed an upregulation of S100 genes at 2 weeks post-infection, and these cells were shown to be involved in leukocyte migration and the innate immune response [49]. In a murine model, the S100A8 gene was also overexpressed in F. hepatica infections [50].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis of PBMCs from sheep revealed an upregulation of S100 genes at 2 weeks post-infection, and these cells were shown to be involved in leukocyte migration and the innate immune response [49]. In a murine model, the S100A8 gene was also overexpressed in F. hepatica infections [50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these approaches are being used to evaluate potential vaccine candidates, identifying the genes involved in conferring protection (Wesołowska et al, 2013;Rojas-Caraballo et al, 2017).…”
Section: Proteomic and Transcriptomic Analysis Of Host Responses To Fmentioning
confidence: 99%
“…The role of H 2 O 2 in F. hepatica infection remains unclear. Transcriptome studies in mice revealed production of ROS as one the most significant pathways undergoing changes during immunoprotection [ 27 ] but it has also been related to oxidative stress and pathology in chronic infection in sheep [ 20 ]. Moreover, different in vitro studies indicate that F. hepatica NEJ possess a unique ability to resist killing by reactive oxygen species released by sheep innate immune effector cells, which may involve the high expression of antioxidant enzymes such as superoxide dismutase, glutathione S-transferase (GST) or peroxiredoxin [ 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that NO and iNOS might play an important role in F. hepatica pathogenesis, possibly as an effective mechanism for killing migrating NEJ, as it has been previously shown to occur in resistant rats [ 31 ] or maybe as an expression of M1 macrophages activation which are known to be related to the development of Th1 responses required for protection [ 18 , 32 , 33 ]. Recent transcriptomic studies have revealed that modifications in the NO signalling pathway may be a necessary condition for immunoprotection in mice [ 27 ] or, on the contrary, downregulation of iNOS might be a paramount factor during the non-protective response occurring in sheep [ 34 ]. In our study, we have not detected an inhibition in NO production in the early phase of infection.…”
Section: Discussionmentioning
confidence: 99%